China : Hong Kong Special Administrative Region Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews economic developments in Hong Kong Special Administrative Region during 1997-98. The paper highlights that beginning in mid-1997, the regional crisis began to erode confidence in Hong Kong's exchange rate and prompted a series of speculative attacks. Pressures on the exchange rate led to sharply higher interest rates, weakened domestic demand, and clouded growth prospects for 1998. The paper provides an update on the transition issues since the transfer of sovereignty on July 1, 1997. Cyclical developments and trends in domestic and external demand and the property market are also analyzed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet